PARTNERSHIP WITH NON-PROFIT ORGANIZATIONS AS A WAY TO INCREASE THE SOCIAL RESPONSIBILITY OF RUSSIAN BUSINESS: A PRACTICE-ORIENTED APPROACH - P. S. Shcherbachenko; M. S. Karlinskaya (Вестник университета)
Recently, the role of social responsibility in forming a company’s business reputation and achieving success in the market has been increasing. Many Russian corporations interact with non-profit organizations when implementing programs and projects in various spheres, including social, economic, and environmental. Based on the analysis of non-financial reporting of Russian corporations, joint programs of the commercial and non-commercial sectors on the example of four companies, operating in various sectors of the economy: PJSC “ Oil Company “Rosneft”, PJSC “VTB Bank”, PJSC “Mining and Metallurgical Company “Norilsk Nickel”, and PJSC “Rostelecom” have been described in the article. The result of this partnership is raising efficiency of social activities of companies, increasing their contribution to solving socially significant problems, improving the welfare of society, protecting the environment, and as a consequence, increasing the level of social responsibility of Russian business as a whole.